2011
DOI: 10.3892/ijmm.2011.647
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M promotes proliferation of ovarian cancer cells through signal transducer and activator of transcription 3

Abstract: Oncostatin M (OSM), a pleiotropic cytokine, has been shown to have distinctive effects in different tissues. In ovarian carcinoma, it is commonly co-expressed together with its receptors but its precise role and the underlying molecular mechanism governing its activity remains unclear. The aim of the present study was to investigate the function of the recombinant human OSM (rH-OSM) in human ovarian cancer. The study demonstrated that rH-OSM promotes the proliferation of SKOV3 ovarian cancer cells. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…For example, our laboratory has studied how Oncostatin M (OSM) induces aggressive cancer cell properties implicated in poor patient outcomes. Elevated levels of OSM in the TME are associated with highly aggressive metastatic cancers and an increased risk of tumor recurrence (chemotherapy resistance) in a variety of tumor types [ 61 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. OSM in the TME may originate from immune cells, adipose tissue, as well as cancer cells [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: The Tme; Supporting E-m and Csc Plasticitymentioning
confidence: 99%
“…For example, our laboratory has studied how Oncostatin M (OSM) induces aggressive cancer cell properties implicated in poor patient outcomes. Elevated levels of OSM in the TME are associated with highly aggressive metastatic cancers and an increased risk of tumor recurrence (chemotherapy resistance) in a variety of tumor types [ 61 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. OSM in the TME may originate from immune cells, adipose tissue, as well as cancer cells [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: The Tme; Supporting E-m and Csc Plasticitymentioning
confidence: 99%
“…Some reports indicated that OSM inhibits tumor growth and metastasis in melanoma [ 12 ], lung cancer [ 13 ], etc. Inversely, OSM has been reported to induce tumor growth and metastasis in ovarian cancer [ 14 ], breast cancer [ 15 ] and osteosarcoma [ 16 ]. The function of dysregulated endogenous OSM in cancer cell lines, including in OSCC cell lines, is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides CD83 , a large number of the CD83 highly-associated genes (Person correlation >0.5, p < 0.01) within ovarian cancer transcriptome showed higher expression in ovarian cancer cells, especially in the EpCAM + /CD45 + subtypes ( Figure S1 ). CD83 highly-associated genes, such as ITGAM , IL1B , CYBB , PIK3R5 , BTK, and OSM , ectopically express in ovarian cancer cells or tissues, involving in ovarian cancer progression, hypoxia networks, and the development of chemoresistance [ 44 , 45 , 46 , 47 , 48 , 49 ]. Finally, we found that ovarian cancer patients’ survival inversely correlated with the level of CD83 expression in 907 ovarian cancer patients (low CD83 expression: 652, the high expression: 255), as patients with high CD83 expression lived significantly shorter compared with their counterparts with low CD83 expression ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%